Estudo da participação da neurotransmissão CRFérgica do núcleo leito da estria terminal (NLET) no controle da função cardiovascular em ratos: envolvimento nas alterações cardiovasculares induzidas pelo estresse crônico variado? - Oliveira, Leandro Augusto de (2020)
The aim of the present study was to investigate the role of CRFergic neurotransmission into bed nucleus of stria terminalis (BNST) on cardiovascular function. We observed that bilateral microinjection of the selective CRF1 antagonist CP376395 into BNST reduced the reflex bradycardia without affecting the tachycardia. Conversely the BNST treatment with antisauvagine-30 decreased heart rate response during medial arterial pressure drop without affecting the reflex bradycardia. These findings provide evidence of an involvement of CRF neurotransmission within BNST in baroreflex activity. Secondly, we assessed the interaction of CRF neurotransmission within BNST with local nitrergic signaling, as well as to investigate an involvement of activation of local NMDA glutamate receptor and nitric oxide (NO) signaling in control of cardiovascular responses to acute restraint stress by BNST CRF neurotransmission in rats. We observed that CRF microinjection into the BNST increased local NO release during restraint stress. Furthermore, bilateral microinjection of CRF into the BNST enhanced both the arterial pressure and heart rate increases evoked by restraint stress, but without affecting the sympathetically-mediated cutaneous vasoconstriction. The facilitation of both pressure and tachycardiac responses to restraint stress evoked by BNST treatment with CRF were completely inhibited by local pretreatment with either the selective NMDA glutamate receptor antagonist LY235959, the selective neuronal nitric oxide synthase (nNOS) inhibitor NPLA, the soluble guanylate cyclase (sGC) inhibitor ODQ or the protein kinase G (PKG) inhibitor KT5923. Taken together, these results provide evidence that BNST CRF neurotransmission facilitate local NMDA-mediated glutamatergic neurotransmission and activates nitrergic signaling, and this pathway is local NMDA-mediated glutamatergic neurotransmission and activates nitrergic signaling, which pathway is involved in control of cardiovascular responses to stress. We investigated the involvement of BNST CRFergic neurotransmission in cardiovascular changes evoked by chronic stress in rats. We identified that exposure to a 10-day chronic variable stress (CVS) protocol decreased expression of both CRF1 and CRF2 receptors within the BNST. These effects were followed by increased arterial pressure and impairment of baroreflex function, but without changes on heart rate. Bilateral microinjection of CP376395, or antisauvagine-30 into the BNST did not affect CVS-evoked arterial pressure increase. Nevertheless, BNST treatment with CP376395 decreased both tachycardiac and bradycardiac responses of the baroreflex in non-stressed rats; but these effects were not identified in chronically stressed animals. BNST pharmacological treatment with antisauvagine-30 decreased the reflex tachycardia in control animals, whereas reflex bradycardiac response was increased in CVS animals. Therefore, the results reported in the present study indicate an involvement of both CRF1 and CRF2 receptors within the BNST in baroreflex impairment evoked by chronic stress. Furthermore, the exposition of rats into the CVS protocol did not change the sucrose preference. However, the pharmacological treatment into BNST with CRF1 antagonist reduced the sucrose preference only in control group. The molecular data resulted in no alteration of the number of CRF neurons into BNST. Last, but not least, when the role of CRF1 receptors into BNST were evaluated during the social model of witness stress, the microinjection of CP376395 into BNST reduced the pressor responses on day 5, without changing others parameters. Altogether, the results of this present thesis show the participation of BNST CRF neurotransmission in the control of cardiovascular function in resting conditions and during acute and chronic aversive situations.